Daytime and nighttime casein supplements similarly increase muscle size and strength in response to resistance training earlier in the day: a preliminary investigation - Joy, J. M.; Vogel, R. M.; Broughton, K. S.; Kudla, U.; Kerr, N. Y.; Davison, J. M.; Wildman, R. E. C.; DiMarco, N. M. (Journal of the International Society of Sports Nutrition, 2018)
Background: Casein protein consumed before sleep has been suggested to offer an overnight supply of exogenous amino acids for anabolic processes. The purpose of this study was to compare supplemental casein consumed earlier in the day (DayTime, DT) versus shortly before bed (NightTime, NT) on body composition, strength, and muscle hypertrophy in response to supervised resistance training. Methods: Thirteen males participated in a 10-week exercise and dietary intervention while receiving 35 g casein daily. Isocaloric diets provided 1.8 g protein/kg body weight. Results: Both groups increased (p < 0.05) in lean soft tissue (DT Pre: 58.3 ± 10.3 kg; DT Post: 61.1 ± 11.1 kg; NT Pre: 58.3 ± 8.6 kg; NT Post: 60.3 ± 8.2 kg), cross-sectional area (CSA, DT Pre: 3.4 ± 1.5 cm2; DT Post: 4.1 ± 1.7 cm2; NT Pre: 3.3 ± 1.6 cm2; NT Post: 3.7 ± 1.6 cm2) and strength in the leg press (DT Pre: 341 ± 87.3 kg; DT Post: 421.1 ± 94.0 kg; NT Pre: 450.0 ± 180.3 kg; NT Post: 533.9 ± 155.4 kg) and bench press (DT Pre: 89.0 ± 27.0 kg; DT Post: 101.0 ± 24.0 kg; NT Pre 100.8 ± 32.4 kg; NT Post: 109.1 ± 30.4 kg) with no difference between groups in any variable (p > 0.05). Conclusions: Both NT and DT protein consumption as part of a 24-h nutrition approach are effective for increasing strength and hypertrophy. The results support the strategy of achieving specific daily protein levels versus specific timing of protein ingestion for increasing muscle mass and performance.